1997
DOI: 10.1118/1.597937
|View full text |Cite
|
Sign up to set email alerts
|

Parametrization of mammography normalized average glandular dose tables

Abstract: Data from existing tables of normalized glandular doses in mammography were parametrized to determine analytical expressions that match tabulated results within known uncertainties. The parametrization was performed for three different target/filter combinations (molybdenum target-molybdenum filter, molybdenum target-rhodium filter, and rhodium target-rhodium filter) and three different breast compositions (100% adipose, 50% adipose-50% glandular, and 100% glandular). The analytical expressions provide the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 2 publications
(6 reference statements)
0
45
0
2
Order By: Relevance
“…This method was applied using the paper published by Sobol and Wu, 15 which provides parameterization equations to calculate DgN for different anode/ filter combinations and different glandularities. The parameterization equations were implemented into our excel workbook using 50% glandularity.…”
Section: Wu's Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was applied using the paper published by Sobol and Wu, 15 which provides parameterization equations to calculate DgN for different anode/ filter combinations and different glandularities. The parameterization equations were implemented into our excel workbook using 50% glandularity.…”
Section: Wu's Methodsmentioning
confidence: 99%
“…MGD is calculated using conversion factors established by Monte-Carlo simulations. Dance et al, [12][13][14] Sobol and Wu, 15 Wu et al, 16 and Boone et al [17][18][19] have established conversion factors that are widely used to estimate MGD. The three models differ slightly in the simulation method, but all reported conversion factors dependent on breast thickness, glandularity, x-ray spectra, and beam quality.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Iran included 246 patients (Bouzarjomehri et al, 2006) and showed that an obtained MGD dose for a 141 complete mammographic examination in that country was 5,57 mGy, which is significantly more in regard to this study and which, most probably, is a consequence of a quality control system which was established late and differences in compressed breast thickness. The mentioned studies did not use conversion factors according to Dance (which are used in this study), but in Austra, Korea and Malaysia one used conversion factors according to Wu (Wu et al, 1991), in Sweden according to Rosenstein and in Iran according to Sobol (Sobol & Wu, 1997). Values of MGD dose for a complete mammographic examination in Bosnia and Herzegovina are 5,0 % higher in regard to results obtained from 300 patients in Malaysia (Jamal et al, 2003) and 7,8 % higher in regard to the most complete study (Young & Burch, 2000) conducted in the Great Britain which included 8745 patients.…”
Section: Patient's Dosesmentioning
confidence: 99%
“…We used the parametrization of normalized average glandular dose tables by Sobol and Wu to determine technique factors that provide equal average glandular doses for different digital techniques. [4].…”
Section: Matching Breast Doses Between Sfm and Ffdm For Various Technmentioning
confidence: 99%